2018
DOI: 10.20961/bise.v4i2.27016
|View full text |Cite
|
Sign up to set email alerts
|

Financial Performance Analysis of SMEs Before and After Initial Public Offering (IPO) on the Indonesia Stock Exchange (IDX)

Abstract: SME funding needs have not been fully met. IPO is one of the efforts that can be done by SMEs to meet these funding needs. However, it is not yet known whether the financial performance of SMEs will increase after conducting an IPO. This study aims to analyze the financial performance of SMEs before and after the IPO. The sample of this study is SMEs that listed on the IDX in 2017, which is as many as five SMEs. SME financial performance is measured through three SME financial ratios, namely liquidity, solvenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 2 publications
2
7
0
4
Order By: Relevance
“…Perusahaan baru yang berbasis teknologi disebut juga dengan digital startup. Digital startup is a young and new technology based companies focused on innovation and growth (Talaia et al, 2016). Menurut Brikman (2015, digital startup merupakan organisasi yang dibuat untuk terus bertumbuh dengan berbasis teknologi pada kondisi lingkungan yang tidak menentu.…”
unclassified
See 2 more Smart Citations
“…Perusahaan baru yang berbasis teknologi disebut juga dengan digital startup. Digital startup is a young and new technology based companies focused on innovation and growth (Talaia et al, 2016). Menurut Brikman (2015, digital startup merupakan organisasi yang dibuat untuk terus bertumbuh dengan berbasis teknologi pada kondisi lingkungan yang tidak menentu.…”
unclassified
“…Untuk dapat bertahan dan berkembang, perusahaan digital startup membutuhkan sumber pendanaan yang baik (Talaia et al, 2016). Berdasarkan riset yang dilakukan oleh CB Insights (2019), 29% kegagalan yang dialami startup disebabkan karena kekurangan dana, dan ini menjadi alasan peringkat kedua atas kegagalan-kegagalan lainnya.…”
unclassified
See 1 more Smart Citation
“…Profitability ratio is measurement of company performance from profit [2]. Profitability ratios are divided by several ratios, including Return on Equity (ROE), Return on Assets (ROA), Net Profit Margin (NPM), and Operational Profit Margin (OPM).…”
Section: Methodsmentioning
confidence: 99%
“…The research conducted was observed using Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM) and Operating Profit Margin (OPM). According to Wahyono [2] changes before and after the IPO are seen in the increased liquidity ratio, while the solvency and profitability ratios have decreased. These changes are not significant before and after the IPO.…”
Section: Introductionmentioning
confidence: 99%